Answer:
Answer: LA=2π rh
Hope this helps! Please mark me Brainliest if it did! Have a nice day!
Step-by-step explanation:
You just want to simplify right?!
45. (a^2b^3)(ab)^-2
= (a^2b^3)(a^-2b^-2)
= b
46. (-3x^3y)^2(4xy^2)
= (-9x^6y^2)(4xy^2)
= -36x^7y^4
47. 3c^2d(2c^3d^5) / 15c^4d^2
= 6c^5d^6 / 15c^4d^2
= 2/5c1/4x^4
48. -10g^6h^9(g^2h^3) / 30g^3h^3
= -10g^8h^12 / 30g^3h^3
= -1/3g^5h^9
49. 5x^4y^2(2x^5y^6) / 20x^3y^5
= 10x^9y^8 / 20x^3y^5
= 1/2x^6 1/3y^3
50. -12n^7p^5(n^2p^4) / 36n^6p^7
= -12n^9p^9 / 36n^6p^7
= -1/3n^3p^2
(Sorry it’s messy it’d look better if my phone could actually put the numbers to the power)
Answer:
Tiffany ate 4 slices of pizza
Step-by-step explanation:
1/4 of 16 is 4
Answer:
203 YD
Step-by-step explanation:
Answer:
The equation would be y = 2x + 3
Step-by-step explanation:
In order to solve this, we first need to find the slope of the line between (-2, 5) and (2, 3). In order to do this, we use the slope formula.
m(slope) = (y2 - y1)/(x2 - x1)
m = (3 - 5)/(2 - -2)
m = -2/4
m = -1/2
Now that we have the original line with a slope of -1/2, we can tell a perpendicular line would have a slope of 2. This is because perpendicular lines have opposite and reciprocal slopes. Now we can use that slope and the given point in point-slope form to get the answer. Be sure to solve for y.
y - y1 = m(x - x1)
y + 7 = 2(x + 5)
y + 7 = 2x + 10
y = 2x + 3